KONSTRUKSI REMAJA PEREMPUAN DI SINETRON - Santoso, Widjajanti M (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
Femininity is a social construction that reproduce the being of woman in dayly life. Being a woman in general is represented by beauty, tall, lean, submissive, kind and thinking more of other people rather that herself. The study shows that being a women is also harrassing and violently do that, in the name of to conquer its femininity. Unfortunately this messages are dominant in television’s soap opera (sinetron), through speech, act and characterizing the role as good and bad, eventually leading to criminal act. For feminist it is significant to identified such social construction in order to have an agenda to negotiate those construction. It is a strategy and also a contribution to have a better represented women in soap opera (sinetron). Keywords: femininity, soap opera, harassment, social construction, women.